Exploring the Paradox of Hope and Ambivalence in Short-lived Japanese Colonialism in Indonesia - Lu, Yunqi (Transactions on Social Science, Education and Humanities Research, 2024)
Unlike the European colonial powers that sought long-term political control and resource exploitation, Japan's colonial ambitions in Southeast Asia primarily emerged during the period of World War II driven by its imperial expansionist goals. The unique nature of Japan's colonial history in Southeast Asia deserves further in-depth research and analysis. This paper explores Japan's colonial policies, highlighting the exploitative nature of its colonial economy and its imperialistic character. While Japan portrayed itself as a liberator and unifier of Asia, opposing Western imperialism, its colonial rule in Southeast Asia, including Indonesia, often involved varying degrees of exploitation, coercion, and brutal repression. Furthermore, this paper argues for an understanding of the complex role that this colonial process played in shaping Indonesia's development trajectory. The analysis explores the impact of Japanese colonialism on Indonesia from various angles, including national consciousness, economy, and cultural dissemination. Additionally, it examines the intricate interactions between Japanese colonial authorities and the Indonesian government, people, and democratic activists, which eventually fueled the independence movement in Indonesia.